2009
DOI: 10.1038/nature08012
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic origins of cell-to-cell variability in TRAIL-induced apoptosis

Abstract: In microorganisms, noise in gene expression gives rise to cell-to-cell variability in protein concentrations1–7. In mammalian cells, protein levels also vary8–10 and individual cells differ widely in responsiveness to uniform physiological stimuli11–15. In the case of apoptosis mediated by TRAIL (TNF related apoptosis-inducing ligand) it is common for some cells in a clonal population to die while others survive – a striking divergence in cell fate. Among cells that die, the time between TRAIL exposure and cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,069
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 962 publications
(1,145 citation statements)
references
References 28 publications
51
1,069
3
2
Order By: Relevance
“…The relevance of such cell-to-cell variability for differential apoptosis induction by TRAIL has been described. 25 It remains speculative whether and which of these features are responsible for the observed differential response in our model.…”
Section: Discussionmentioning
confidence: 89%
“…The relevance of such cell-to-cell variability for differential apoptosis induction by TRAIL has been described. 25 It remains speculative whether and which of these features are responsible for the observed differential response in our model.…”
Section: Discussionmentioning
confidence: 89%
“…Cell behaviour and phenotype are directly controlled by dynamic networks of protein interactions in response to external or internal cues/stimuli (Figures 1, 2). Signalling networks, such as those regulated by kinases and phosphobinding domains (eg the SH2 domains) are essential for the integrative response a cell must make at any given point in time to extra-or intracellular cues [4][5][6][7][8][9][10][11].…”
Section: The Cue Signal and Response Model Of Cell Signallingmentioning
confidence: 99%
“…In a similar study, the MIT labs showed how common information processing mediates cell-specific responses to stimuli [5]. Therefore, to fully understand a cellular response to a perturbation (such as to a drug), it is essential to analyse this in the context of the cell's multivariate state [5][6][7]. This observation does not just have implications for biomarker discovery, as discussed below, but also for how analysis of biological systems should be performed.…”
Section: Multivariate Nature Of Cellular Networkmentioning
confidence: 99%
See 2 more Smart Citations